1997
DOI: 10.1103/physreve.56.r29
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on biased random walks in disordered media

Abstract: We study diffusion on an energetically disordered lattice, where each bond between sites is characterized as a random energy barrier. In such a model it had previously been observed that the mean square displacement is sublinear with time at early times, but eventually reaches the classical linear behavior at long times, as a strong function of the temperature. In the current work we add the effect of directional bias in the random walk motion, in which along one axis only, motion in one direction is assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In the most works in which the concept of the correlation times distribution has been discussed, it was assumed that the randomness of correlation times appears due to a static set of random barriers and an atom (or molecule) moves without changing them. However, randomness of potential barriers must be dynamic rather than static, since, due to the collective character of the diffusion process, the fluctuations of the potential barriers would occur simultaneously with each jump of a moving particle [39][40][41]. Now we consider the transformations of the second moment of NMR line shape for the case, when the potential barrier for the mobility of magnetic nuclei is the stochastic function of the time.…”
Section: Nmr and Dynamic Disorder In Solid Statementioning
confidence: 99%
“…In the most works in which the concept of the correlation times distribution has been discussed, it was assumed that the randomness of correlation times appears due to a static set of random barriers and an atom (or molecule) moves without changing them. However, randomness of potential barriers must be dynamic rather than static, since, due to the collective character of the diffusion process, the fluctuations of the potential barriers would occur simultaneously with each jump of a moving particle [39][40][41]. Now we consider the transformations of the second moment of NMR line shape for the case, when the potential barrier for the mobility of magnetic nuclei is the stochastic function of the time.…”
Section: Nmr and Dynamic Disorder In Solid Statementioning
confidence: 99%
“…Earlier, 10,11 we found that if a bias is applied, then there is a crossover time after which the mode of motion switches from a predominantly random walk to a ballistic one. The transition time depends on the jump probability and the height of the bias.…”
Section: Introductionmentioning
confidence: 97%
“…In many models, the nonsymmetric behavior is due to the retention of memory of the previous step, resulting in enhanced diffusion. In our previous work, 10,11 this was due to an external field leading to a ballistic motion in the long time limit. On the other hand, when the bias alternates at a given frequency ν ) 1/2τ (τ is the time it takes to change the direction of the bias) the mean square displacement was found to be proportional to time t, a behavior typical of a stochastic random walk.…”
Section: Introductionmentioning
confidence: 97%
“…In the latter case, the lattice sites (or bonds) are assigned different energy states and, consequently, the walker is biased towards sites corresponding to potential wells (or small energy barriers). Moreover, disorder can be deterministic or random and it can be dynamic (the environment is renewed at each jump of the walker) [1,10], or static (the environment is frozen in a particular configuration) [11,12]. Particles diffusing on such structures can also be endowed with memory effects [13,14], or be influenced by the distribution of other diffusing particles on the same structure [15].…”
Section: Introductionmentioning
confidence: 99%